PROPHYLAXIS AND TREATMENT OF RESPIRATORY DISEASES AND FREQUENTLY AILING CHILDREN WITH TOPICAL BACTERIAL LYSATES - M.S. Savenkova; A.A. Afans'eva; V.S. Minasyan; S.I. Tyurkina ("Paediatrician" Publishers LLC, 2009)
The share of acute respiratory infections is more than 90% of all diseases of upper airways. It mostly related with insufficiency of immunological defense, which elements are localized in different organs, including mucous tunic of upper airways. The article presents the data on high effectiveness of complex treatment of frequently ailing children with respiratory infection, including topical immunomodulator IRS 19 (bacterial lysates mixture). Its administration combined with antibiotics and antiviral medications allowed achieving more rapid fauces sanation. In particular, significant decreasing of pathogenic and conditionally pathogenic micro flora (neumococcus, neisseria, and Staphylococcus aureus) was marked in 3 months after the beginning of treatment.Key words: frequently ailing children, acute respiratory infections, etiotropic therapy, bacterial lysates mixture.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):92-96)